Ethics and values in project management stages in construction industry - Sami, Fatma Al-Zahraa; Abdul Rahim, Asiah (IIUM Press, 2015)
The main aim of this paper is to examine the awareness of the principles of ethics among the professionals in Project Management in construction industry. The objectives of this paper are as follows: Firstly, to compare and review between the concept of ethics from Western and Islamic perspective by evaluating the principles and practice of ethics when the professionals carry out their duty. Secondly, to investigate the wide range of ethical problems faced at project management stages during construction period. Thirdly, to explore solutions that can be utilized and applied among professionals in construction industry. Previous studies showed that ethics and values is the branch of philosophy that investigates morality and the ways of thinking that guide human behavior. Ethics involve examining moral standards of society and asking how these standards are reasonable or unreasonable. In the construction industry there are two main levels to consider in relation to ethics and values in terms of professionals and corporate/organizational ethics. Professional’s ethics refer to the behavior expected of individual or industry or a group within the industry that was bound by a set of principles. However, it appears that in practice professionals in the building industry deemed to behave unethical when implementing project management on various stages. This arises negative impact and causes a number of problems to the public. The methodology applied will be table research to professionals for project management stages in construction industry in Malaysia. The outcome of this paper will benefit the professionals in applying good ethics and values in various stages in of project management in construction industry terms of awareness and its application.